Implicazioni cliniche ed economiche di tramadolo SR - Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Tramadol is one of the preferred weak opioid agonists in the management of chronic pain, due to a good efficacy and safety profile, to a particularly low interference with cardiovascular and respiratory functions and a low dependence and abuse potential. The successful use of tramadol, nevertheless, is often limited by low patient compliance, a consequence of gastrointestinal side effects (mainly nausea and vomiting) and frequent dosing regimens, among other reasons. In this paper, clinical studies conducted on slow-release formulations of tramadol and other strategies for compliance improvement in various pain conditions are reviewed. From the examined literature, it appears that the strategy with the best compliance is the use of slow release (SR) formulations, which simplify dosing regimens and tend to have a somewhat better tolerability, and a slow dose escalation, which improves tolerability. The advantages of SR formulations have to be weighed against the superior acquisition cost and the slower onset of analgesia. A frame for the evaluation of the clinical and economical advantages and disadvantages of SR versus immediate release formulations of tramadol is also proposed.